Application of Fungicides Against Postharvest Botrytis Bunch Rot of Table Grapes in the Western Cape - de Kock, P.J.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Fungicide programmes for the control of postharvest Botrytis bunch rot on table grapes were evaluated in six trials from 1984/85 to 1991/92 in the Western Cape. The study demonstrated the ineffectiveness of dicarboximide applications during bloom to early pea size in well managed vineyards. Dicarboximides were most effective when applied from bunch closure to ripening.  lprodioue/sulphur treatments at veraison and before harvest reduced Botrytis bunch rot, but they were ineffective in inhibiting infection during storage. Control was only achieved when grapes were exposed to S02 during storage. Although bunch dip treatments reduced infection in the vineyard, this control was not commercially acceptable.  Therefore no real advantage was found when bunches were dipped in fungicide at veraison to ensure better coverage. The fact that berries became infected primarily during harvest, package operations and storage, emphasised the necessity for reducing B. cinerea inoculum on harvested grapes. It is suggested that the results of this investigation may lay the foundation for incorporating biological control in Botrytis bunch rot control.